2021
DOI: 10.3390/biom11050691
|View full text |Cite
|
Sign up to set email alerts
|

Some CSF Kynurenine Pathway Intermediates Associated with Disease Evolution in Amyotrophic Lateral Sclerosis

Abstract: The aim of this study was to evaluate the kynurenine pathway (KP) and amino acids profile, using mass spectrometry, in the cerebrospinal fluid (CSF) of 42 amyotrophic lateral sclerosis (ALS) patients at the diagnosis and 40 controls to detect early disorders of these pathways. Diagnostic and predictive ability (based on weight loss, forced vital capacity, ALS Functional Rating Scale—Revised evolution over 12 months, and survival time) of these metabolites were evaluated using univariate followed by supervised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…To explore further tissue inflammation after acoustically-mediated BBBO, a previously described targeted metabolomic approach using HPLC-MS was applied ( Lefevre et al, 2019 ; Alarcan et al, 2021 ). We dosed the TRP derivates, especially metabolites from the KP cascade in the brain tissue, in the CSF, and in the blood serum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To explore further tissue inflammation after acoustically-mediated BBBO, a previously described targeted metabolomic approach using HPLC-MS was applied ( Lefevre et al, 2019 ; Alarcan et al, 2021 ). We dosed the TRP derivates, especially metabolites from the KP cascade in the brain tissue, in the CSF, and in the blood serum.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the effects of acoustically-mediated BBBO on neurotransmission have never been investigated; this study explored these bioeffects by dosing 5-HT and its derivates originating from the TRP metabolism by a targeted HPLC-MS approach ( Lefevre et al, 2019 ; Alarcan et al, 2021 ). Indeed, the striatum is involved in dopaminergic, cholinergic, and GABAergic neurotransmissions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of KYNA in human cerebrospinal fluid has been repeatedly reported ( Table S2 ). The content of KYNA in cerebrospinal fluid obtained from adult healthy humans ranges from 0.0009 to 0.005 μM [ 16 , 20 , 21 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. The content of KYNA in cerebrospinal fluid obtained from children is within the same limits [ 38 ].…”
Section: Distribution Of Kynurenic Acidmentioning
confidence: 99%
“…QUIN was significantly elevated in neurons and microglia in the cerebrospinal fluid, motor cortex, and spinal cord of ALS patients, while cerebrospinal fluid IDO, TRP, and KYN were significantly elevated, and the 3-HK/KYNA and QUIN/KYNA ratios tended to be elevated ( 131 ). Since QUIN and 3-HK may have neurotoxic and KYNA neuroprotective effects, these findings may reflect the impairment of neurotoxic compounds by KP ( 149 ). It has been found that both reduced and elevated NMDAR functions are associated with autism spectrum disorder (ASD), and its deviation in either direction leads to ASD, demonstrating the importance of a normal range of NMDAR function.…”
Section: Trp Metabolism In Neurological and Psychiatric Disordersmentioning
confidence: 99%